Overview of Older Consumer Behavior - Moschis G.P. (2023)
Developing an effective marketing strategy to appeal to the older consumer market requires a deep understanding of the reasons for the behaviors of the large and diverse older consumer market. It requires understanding how older consumers differ from younger consumers, and most importantly the reasons consumer needs and behaviors differ between the older generations, as people become increasingly heterogeneous with age in later life. The information presented in this chapter suggests that differences in needs and behaviors in later life are the result of three main types of factors: aging, life circumstances and life-changing events older persons experience at various times in their lives. These three types of factors affect an older person’s psychological states—i.e., needs, attitudes, motives, and values, which in turn affect his or her consumer behaviors. Theories from various disciplines and research findings of studies on older consumers are used to explain observed differences in older consumers’ behavior.